INTERNATIONAL CORPORATE TAX AVOIDANCE: A REVIEW OF THE CHANNELS, MAGNITUDES, AND BLIND SPOTS. (20th January 2019) - Beer, Sebastian; de Mooij, Ruud; Liu, Li
Abstract: This paper reviews the rapidly growing empirical literature on international tax avoidance by multinational corporations. It surveys evidence on the main channels of corporate tax avoidance including transfer mispricing, international debt shifting, treaty shopping, tax deferral, and corporate inversions. Moreover, it performs a meta‐analysis of the extensive literature that estimates the overall size of profit shifting. We find that the literature suggests that, on average, a 1 percentage‐point lower corporate tax rate will expand before‐tax income by 1%—an effect that is larger than reported as the consensus estimate in previous surveys and tends to be increasing over time. The literature on tax avoidance still has several unresolved puzzles and blind spots that require further research.